2016
DOI: 10.5755/j01.ee.27.1.10267
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Customer Loyalty Program on Organizational Performance: a Case of Airline Industry

Abstract: Loyalty programs enhance airline's value proposition. Yet little is known about how customer loyalty programs affect organizational performance. This understanding is important because airlines must decide what design of loyalty program to choose in order to maximize the revenue, profit and the number of passengers. The authors develop and test theory proposing that specific design of loyalty program ensures better organizational performance. The purpose of this study is to examine the influence of loyalty pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…For the industry players though, there is currently more than sufficient research on the necessity of customer loyalty programs and the attached importance they bring to business enterprises world over (Beck et al, 2015;Magatef & Tomalieh, 2015;Sharp & Sharp, 1997;Jang & Mattila, 2005;Vilkaite-Vaitone & Papsiene, 2016). Using loyalty programs to manage customer-company relations has been a master-stroke in enhancing the former's retention thereby reducing marketing costs which is something the passenger transportation sector in the country will be well advised to embrace (Kang et al, 2015).…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…For the industry players though, there is currently more than sufficient research on the necessity of customer loyalty programs and the attached importance they bring to business enterprises world over (Beck et al, 2015;Magatef & Tomalieh, 2015;Sharp & Sharp, 1997;Jang & Mattila, 2005;Vilkaite-Vaitone & Papsiene, 2016). Using loyalty programs to manage customer-company relations has been a master-stroke in enhancing the former's retention thereby reducing marketing costs which is something the passenger transportation sector in the country will be well advised to embrace (Kang et al, 2015).…”
Section: Problem Statementmentioning
confidence: 99%
“…Many of the literature reviewed spent much of their focus on how loyalty programs enhance organisational performance through customer retention. Measuring of competitive advantage and measuring their effects of financial performance (Magatef & Tomalieh, 2015;Beck et al, 2015;Basera, 2014;Liu & Yang, 2009;Vilkaite-Vaitone & Papsiene, 2016). However, Berman (2006) and Furinto et al (2009) introduced contrasting views that focus on how loyalty programs are designed as being the most valuable process in their success.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Authors consider loyalty cards as a tool for creating a long-term, profitable relationship between seller and customer based on satisfaction (Plazibat, Šušak, & Šarić, 2016;Vilkaite-Vaitone & Papsiene, 2016). A number of authors (Plazibat et al, 2016;Vesel & Zabkar, 2009) believe that loyalty cards are made with the initial objective to increase the number of repeat purchases in sectors with strong competition, but taking into account that brand value is not decreasing.…”
Section: Significance and Expected Benefits From Loyalty Cardsmentioning
confidence: 99%
“…Companies spend billions on the development of customers' loyalty, while scientists write numerous articles on this topic. For a long time, it was mainly related to B-2-C markets, but it seems that loyalty is essential for the business-to-business markets as well (Skarmeas et al, 2016;Vaitone-Vilkaite & Papsiene, 2016). The previous research showed that satisfaction is the key determinant of customer loyalty (Wirtz et al, 2014;Askariazad & Babakhani, 2015).…”
Section: Introductionmentioning
confidence: 99%